Assessing Exercise Limitation Using Cardiopulmonary Exercise Testing - Michael K. Stickland; Scott J. Butcher; Darcy D. Marciniuk; Mohit Bhutani (Pulmonary Medicine)
The cardiopulmonary exercise test (CPET) is an important physiological investigation that can aid clinicians in their evaluation of exercise intolerance and dyspnea. Maximal oxygen consumption (V˙O2max) is the gold-standard measure of aerobic fitness and is determined by the variables that define oxygen delivery in the Fick equation (V˙O2 = cardiac output × arterial-venous O2 content difference). In healthy subjects, of the variables involved in oxygen delivery, it is the limitations of the cardiovascular system that are most responsible for limiting exercise, as ventilation and gas exchange are sufficient to maintain arterial O2 content up to peak exercise. Patients with lung disease can develop a pulmonary limitation to exercise which can contribute to exercise intolerance and dyspnea. In these patients, ventilation may be insufficient for metabolic demand, as demonstrated by an inadequate breathing reserve, expiratory flow limitation, dynamic hyperinflation, and/or retention of arterial CO2. Lung disease patients can also develop gas exchange impairments with exercise as demonstrated by an increased alveolar-to-arterial O2 pressure difference. CPET testing data, when combined with other clinical/investigation studies, can provide the clinician with an objective method to evaluate cardiopulmonary physiology and determination of exercise intolerance.